The Effect of Different Fertilizer Treatments of Plant Traits on Faba Bean during Flowering Periods - M Tunç; F Başdemir; S Ipekeşen; S Eliş; R Parildar; B.T Biçer (Journal of Agronomy, Technology and Engineering Management, 2022)
The experiment was conducted at Dicle University Field Crops Department, Southeast Anatolia, Diyarbakir Turkey in the 2018-2019 early spring growth periods. The study aimed to determine the effect of fertilizer treatments (control, phosphorus, nitrogen, organic, and Rhizobium) on plant traits of different faba bean cultivars (Filiz 99, Eresen 87, and Salkim). Plants were harvested in three different periods pre-flowering (43-62 days after sowing), full-flowering (52-75 days), and post-flowering (78-98 days), and shoot and root traits were evaluated. Fresh plant biomass, stem height, fresh and dry root weight, fresh and dry nodule weight, fresh leaf weight, and fresh and dry pod weight were responding to nitrogen fertilizer treatments depending on flowering periods. The number of nodules and fresh and dry nodule weight was affected to a different degree in both nitrogen and phosphorus fertilizer treatments. Nodule weight showed a negative response to rhizobium inoculation. We determined that nitrogen (40 kg ha-1) and phosphorus (80 kg ha-1) fertilizer treatments on faba beans were important. However, we have not belied that fertilizer applications should not be applied for sustainable agriculture because of their high environmental efficiency.